Analysis of the Relationship between Mass and Spring Constant through PheT Simulations - Widya Noerafifah, Dinna; Fikri, Fikri; Nurfadilla, Dilla; Malik , Adam (Al-Khazini: Jurnal Pendidikan Fisika, 2025)
Springs can be found in various shapes and sizes depending on the application. Springs can be used to store energy, maintain position or dampen vibrations, and also to produce the necessary force in mechanical systems. This research was carried out using a virtual lab based on phet simulations. Phet simulations are simulations that can be used by teachers in teaching fraction material in class. The method used in this research uses a quantitative method by processing practical statistical data virtually. The data can be measured and calculated directly and the explanation is expressed in numbers or figures. The technique used in collecting data is by carrying out several experiments and entering different variable values. From this research, the results obtained are that gravity has a directly proportional relationship to the amount of potential energy of the spring. The greater the weight force acting on the spring system, the greater the potential energy of the spring.